Evaluation of Bronchoalveolar Lavage Fluid Cytokines as Biomarkers for Invasive Pulmonary Aspergillosis in At-Risk Patients - Gonçalves, Samuel M.; Lagrou, Katrien; Rodrigues, Cláudia S.; Campos, Cláudia F.; Bernal-Martínez, Leticia; Rodrigues, Fernando; Silvestre, Ricardo; Alcazar-Fuoli, Laura; Maertens, Johan A.; Cunha, Cristina; Carvalho, Agostinho (Frontiers in Microbiology, 2017)
Background: Invasive pulmonary aspergillosis (IPA) is an infection that primarily affects immunocompromised hosts, including hematological patients and stem-cell transplant recipients. The diagnosis of IPA remains challenging, making desirable the availability of new specific biomarkers. High-throughput methods now allow us to interrogate the immune system for multiple markers of inflammation with enhanced resolution. Methods: To determine whether a signature of alveolar cytokines could be associated with the development of IPA and used as a diagnostic biomarker, we performed a nested case-control study involving 113 patients at-risk. Results: Among the 32 analytes tested, IL-1β, IL-6, IL-8, IL-17A, IL-23 and TNFα were significantly increased among patients with IPA, defining two clusters able to accurately differentiate cases of infection from controls. Genetic variants previously reported to confer increased risk of IPA compromised the production of specific cytokines and impaired their discriminatory potential towards infection. Collectively, our data indicated that IL-8 was the best performing cytokine, with alveolar levels ≥904 pg/mL predicting IPA with elevated sensitivity (90%), specificity (73%), and negative predictive value (88%). Conclusions: These ﬁndings highlight the existence of a specific proﬁle of alveolar cytokines, with IL-8 being the dominant discriminator, which might be useful in supporting current diagnostic approaches for IPA.